Scanning electrochemical microscopy characterization of energy materials - Moghaddam, Mahdi (fi=Turun yliopisto|en=University of Turku|, 2023)
Replacing hydrocarbon-based energy production systems with alternative, low carbon footprint ones is an urgent necessity. Advancing in this direction requires a thorough understanding of local electrochemical conversion and storage mechanisms at the interface of energy materials, which are key components of alternative energy systems. In this thesis, utilizing scanning electrochemical microscopy (SECM), novel insights are presented on two main groups of energy materials. As for conversion, the presence of oxygen in electrocatalyst layers of polymer electrolyte membrane fuel cells was investigated. Using SECM in feedback mode, it was confirmed that co-existance of Nafion and carbon black leads to confinement of oxygen. It was suggested that oxygen is confined to the hydrophobic parts of self-assembled Nafion on the graphitic surfaces of the carbon black used as the catalyst support. As for storage, charge transfer in solid active particles utilized as solid boosters for flow batteries was studied. First, the configuration where solid boosters are added to the tank of flow batteries was conceptualized. It was shown that the total accessible state of charge of the solid depends on the redox potential mismatch between the solid and the electrolyte. The smaller the mismatch, the higher the stored charge. In addition, it was shown that booster’s available surface area is a critical technical requirement for operation of solid boosted flow batteries. In case of equal exchange current densities, the active surface area of the booster should be at least three times larger than that of electrode in the cell to drive the electrochemical reactions on the booster at a reasonable rate. Lastly, the behavior of copper hexacyanoferrate (CuHCF) booster microparticles was investigated at micro and nano scales combining SECM and optical microscopy. SECM tip was used, in a novel approach, as an optical mirror in addition to electrochemical triggering to enable mapping of the local conversion rates and states-of-charge, revealing a homogeneous surface conversion of nanocrystallites at short time followed by a slower heterogeneous bulk conversion. The heterogeneity is likely originating from locally different porosities or different nanocrystal size distribution.